A pedagogical proposal in the preparation and administration of medicines and solutions: articulating nursing and mathematics in teaching (Research, Society and Development, 2023)
The aim of this study is to describe a pedagogical proposal on the preparation and administration of medicines and solutions relating the areas of knowledge of Nursing and Mathematics. This is a qualitative, descriptive study related to a pedagogical proposal based on two teaching strategies and a pedagogical resource related to the preparation and administration of medicines and solutions, relating the knowledge of the areas of Nursing and Mathematics. This pedagogical proposal was elaborated by students of the Doctoral course in Teaching, in the discipline of Teaching Strategies II. The activity in the discipline occurred through a work, integrating the areas of action of doctoral candidates in the context of the classroom. It was verified the importance of integration between the areas of Nursing and Mathematics and the use of mechanisms that can link the context of students and the teaching and learning processes in academic training on the preparation and administration of medicines and solutions. Thus, it is relevant to insert differentiated teaching strategies aimed at providing aspects of interaction and dialogue between students and teachers, stimulating the learning of the contents of the discipline and professional training.